2022
DOI: 10.1021/acsami.2c14636
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Optimized Carrier and Phonon Transport Properties in Bi–Cu2S Coalloyed GeTe

Abstract: GeTe is an emerging lead-free thermoelectric material, but its excessive carrier concentration and high thermal conductivity severely restrict the enhancement of thermoelectric properties. In this study, the synergistically optimized thermoelectric properties of p-type GeTe through Bi−Cu 2 S coalloying are reported. It can be found that the donor behavior of Bi and the substitution−interstitial defect pairs of Cu + ions effectively reduce the hole concentration to an optimal level with carrier mobility less af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…An ideal TE material requires a large Seebeck coefficient, high electrical conductivity, and low thermal conductivity. [4][5][6] Since the three parameters are intrinsically coupled with one another, it is difficult to signicantly optimize the TE performance by adjusting a single variable. Previous strategies have been proved to achieve higher zTs, such as tuning the carrier concentration to an optimal level, [7][8][9][10] band structure engineering to enhance the power factor S 2 s by promoting band convergence [11][12][13][14][15] or inducing a resonant level, [16][17][18][19] and phonon engineering to suppress the lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal TE material requires a large Seebeck coefficient, high electrical conductivity, and low thermal conductivity. [4][5][6] Since the three parameters are intrinsically coupled with one another, it is difficult to signicantly optimize the TE performance by adjusting a single variable. Previous strategies have been proved to achieve higher zTs, such as tuning the carrier concentration to an optimal level, [7][8][9][10] band structure engineering to enhance the power factor S 2 s by promoting band convergence [11][12][13][14][15] or inducing a resonant level, [16][17][18][19] and phonon engineering to suppress the lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkably high peak zT values of above 2.0 have been achieved in GeTe-based materials. [44][45][46][47][48][49][50][51][52][53][54] For instance, by band convergence induced by Pb, Bi, and Mn co-doping, an enhanced zT of 2.3 is achieved in the cubic Ge 0.82 Pb 0.1 Bi 0.04 Mn 0.04 Te at 573 K. [50] Tailoring grain boundary via Ga 2 Te 3 precipitates combined with Sb and Pb co-alloying enables a peak zT of 2.1 at 773 K in the cubic Ge 0.78 Ga 0.01 Pb 0.1 Sb 0.07 Te. [54] The excellent TE performance makes GeTe a potential system for power generation applications in the medium temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The n opt of GeTe at its operating temperature range is theoretically estimated to be 1-3 × 10 20 cm −3 (Figure 1a), using the single parabolic band (SPB) model. [59] In light of the over-high n H in the as-fabricated binary GeTe, the counter doping, using aliovalent elements, such as Bi [33,42,46,47,50,[60][61][62][63] and Sb, [27][28][29][30][31]34,[39][40][41]43,[51][52][53] is a common method for reducing the over-high n H to n opt . In addition, previous studies also found that n H can be reduced by increasing the formation energy of Ge vacancies (V Ge ) through hetero-alloying.…”
Section: Introductionmentioning
confidence: 99%